CARBOXYLIC ACIDS ELECTROOXIDATION ON SHUNGITE ELECTRODE - Davydenko, Oleksandr; Ledovskykh, Volodymyr (Proceedings of National Aviation University (archive), 2017)
Purpose: This article discusses the electrochemical method of directional conversion of carboxylic acids, which are the most aggressive hydrocarbons oxidation products back into the corresponding hydrocarbons. Existing methods for the regeneration of waste petroleum oils have significant drawbacks, which include the formation of new hard-reclaimed waste and loss of a significant part of the oil during regeneration. Methods: Electrooxidation processes of carboxylic acid on various electrode materials: platinum, graphite and shungite anodes were studied. Results: Potentiostatic polarization curves with simultaneous measurement of near-electrode solution pH showed differences in the process on these anode materials: dimer yield for Kolbe is decreased under the transition from platinum to shungite. At potentials higher than 2.0 v, carboxylic acid has a higher adsorbability compared to water. Therefore Faraday’s side-process of water oxidation doesn’t almost occur, which contributes to high yield of expected product according to current. Electrolysis of carboxylic acids solutions under controlled potential (2.0 and 2.4 V) and chromatographic analysis of the formed products showed that along with the dimeric structures formation for Kolbe reaction, the occurrence of a hydrocarbons mixture takes place, which may be the result of disproportionation of hydrocarbon radicals (alkane and alkene ) and hydrocarbons of isomeric structure, by further oxidation of the hydrocarbon radical to carbocation and its subsequent transformation into the corresponding saturated and unsaturated isomers. Such statement is not supported by conception of the process of one- and two-electron carboxylic acid oxidation. Discussion: General carboxylic acid oxidation scheme according to one-electron mechanism (dimerization and disproportionation of the radical) and two-electron mechanism (formation and carbocation rearrangement) is proposed. The formation of hydrocarbons under carboxylic acid electrooxidation of waste oils during their regeneration can promote the increase of oil yield without formation of dangerous by-products.